Brand Identity Nagari Pariangan, Desa Terindah di Dunia Kabupaten Tanah Datar, Sumatera Barat - Muhammad Syukri Erwin; Zainal Warhat; Syafwandi Syafwandi (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
ABSTRACTA city of Pariangan is an old city in Minangkabau. A city called as the area of origin of the ancestors of the Minangkabau people that have a lot of potential both natural beauty and culture that is still exist and protected. Through the design of brand identity, the various potentials in the city of Pariangan is such a beautiful way that the creation of an effective promotional activities. So it can increase the number of tourists visiting both local and foreign. This will affect the economic sector of the community, either directly or indirectly. In the application of the concept that is inspired from the unique visual design of Pariangan city. Like the illumination motif of the ancient manuscript of Pariangan such as